Assessing the efficacy of the trim and fill method in adjusting for publication bias in meta analysis - Nik Idris, Nik Ruzni; Sarudin, Norraida (2012)
One of the most common critics leveled against meta-analysis pertains to the issue of publication bias. A publication bias may be encountered if a meta analysis is restricted to the combination of results obtained from studies which have been published. The bias occur when unpublished studies are associated with their outcomes, namely, studies which produced small effects or negative results are more likely not to get published. The most common method used to adjust for publication bias is the Duvall and Tweedie’s Trim and Fill method. The method relies on the scrutiny of one side of a funnel plot for asymmetry which is assumed to be due to publication bias. In most of the studies investigating the performance of this method, binary meta analysis data were used, utilizing the effect size measures such as the odds ratio, or risk relative. The main aim of this study is to evaluate the efficacy of the Trim and Fill method in correcting the publication bias in meta analysis of continuous data with standardized mean difference as the measure of effects.